Roadmap on plasticity and epigenetics in cancer. (1st May 2022) - Foo, Jasmine; Basanta, David; Rockne, Russell C; Strelez, Carly; Shah, Curran; Ghaffarian, Kimya; Mumenthaler, Shannon M; Mitchell, Kelly; Lathia, Justin D; Frankhouser, David; Branciamore, Sergio; Kuo, Ya-Huei; et al.
Abstract: The role of plasticity and epigenetics in shaping cancer evolution and response to therapy has taken center stage with recent technological advances including single cell sequencing. This roadmap article is focused on state-of-the-art mathematical and experimental approaches to interrogate plasticity in cancer, and addresses the following themes and questions: is there a formal overarching framework that encompasses both non-genetic plasticity and mutation-driven somatic evolution? How do we measure and model the role of the microenvironment in influencing/controlling non-genetic plasticity? How can we experimentally study non-genetic plasticity? Which mathematical techniques are required or best suited? What are the clinical and practical applications and implications of these concepts?